The practices of mathematics education doctoral students - Monaghan, John (Educação Matemática Pesquisa Revista do Programa de Estudos Pós-Graduados em Educação Matemática, 2019)
This paper looks at the practices (or praxeologies) of mathematics education doctoral students and their supervisors from the perspectives of activity theory and the anthropological theory of the didactic. The paper examines three ways to view mathematics education research before discussing : research methods and methodologies ; the debate on qualitative and quantitative research ; and implications for the supervision of doctoral students. Este artículo observa las prácticas (o praxeologías) de estudiantes de doctorado en Educación Matemática y sus directores desde las perspectivas de la Teoría de la Actividad y de la Teoría Antropológica de lo Didáctico. El artículo examina tres modos de ver la investigación en Educación Matemática previa a la discusión: métodos de investigación y metodologías, el debate entre investigación cualitativa y cuantitativa y las implicaciones para la dirección de estudiantes de doctorado.